CD47 stabilizes ROBO2 to regulate glioblastoma progression by preventing ITCH-mediated ubiquitination - Ruhi Polara; Briony L. Gliddon; Raja Ganesan; Lorena T. Davies; John Toubia; Sakthi Lenin; Ghizal Siddiqui; Olivia Morris-Hanon; Melinda N. Tea; Paul A. B. Moretti; Dung A. Nguyen; Chung Hoow Kok; et al. (Proceedings of the National Academy of Sciences, 2026)
CD47 is an innate immune checkpoint that inhibits phagocytosis by myeloid cells, contributing to immune evasion by cancer cells. CD47-blocking antibodies have limited efficacy in glioblastoma (GBM), and the cell-intrinsic role of CD47 is poorly understood. In this study, we show that CD47 is highly expressed at the invasive edge of GBM tumors, and its elevated expression correlates with poor patient survival. We demonstrate that CD47 loss impairs GBM cell proliferation, migration, and invasion, independent of immune activity, and leads to reduced tumor burden and prolonged survival in vivo. Our study identifies ROBO2 signaling as a key downstream effector of CD47 and demonstrates that loss of ROBO2 similarly reduces GBM cell proliferation and migration. Importantly, we have uncovered that CD47 stabilizes ROBO2 by sequestering the E3 ubiquitin ligase ITCH, thereby blocking ubiquitination and proteasomal degradation of ROBO2. These findings establish CD47 as a key regulator of GBM cell plasticity and highlight the therapeutic potential of targeting CD47 – ROBO2 signaling in GBM.